Transitory Citizens: contentious Housing Practices in Contemporary South Africa - Chance, Kerry Ryan (Plural, 2018)
This article examines the informal housing practices that the urban poor use to construct, transform, and access citizenship in contemporary South Africa. Following the election of Nelson Mandela in 1994, the provision of formalized housing for the urban poor has become a key metric for ‘non-racial’ political inclusion and the desegregation of apartheid cities. Yet, shack settlements—commemorated in liberation histories as apartheid-era battlegrounds—have been reclassified as ‘slums’, zones that are earmarked for clearance or development. Evictions from shack settlements to government emergency camps have been justified under the liberal logic of expanding housing rights tied to citizenship. I argue that the informal housing practices make visible the methods of managing ‘slum’ populations, as well as an emerging living politics in South African cities.